Denmark : Financial Sector Assessment Program; Detailed Assessment of the Securities Clearance and Settlement Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Detailed Assessment of the Securities Clearance and Settlement Systems for Denmark. The assessment recommends that securities settlement systems should have a well-founded, clear, and transparent legal basis in the relevant jurisdiction. Confirmation of trades between market participants should occur as soon as possible after trade execution, but no later than trade date (T+0). Where confirmation of trades by indirect market participants is required, it should occur as soon as possible after trade execution, preferably on T+0, but no later than T+1.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet